จุลินทรีย์เซลลูโลสิกเพื่อการย่อยสลายเซลลูโลส : การนำไปใช้ประโยชน์ทางเกษตร : รายงานวิจัย - วรวุฒิ จุฬาลักษณานุกูล (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The aim of this research is to use cellulosic microorganism in agricultural application. Ethanol production by thermotolerant yeasts have been extensively studied, because thermotolerant yeasts are capable of growth and fermentation during the summer months in non-tropical countries as well as under tropical climates. The result revealed that 7 from 25 isolate show to be thermotolerant xylose-utilizing yeasts for ethanol production from rice straw. Yeast-malt extract medium was used to isolate thermotolerant yeasts at 35, 37, 40, 45 and 50°C. SKN 2-1 was showing producing highest yield of ethanol compared to other isolates. SKN 2-1 could grow and produce ethanol at 40 and 45°C. The thermotolerant yeast isolate SKN 2-1 produced the highest concentration of ethanol 0.66 and 0.87 g L⁻¹ which was equivalent 7.67 and 10.10 of the theoretical ethanol yield r at 40 and 45°C using rice straw contained cellulose 37.67± 0.31%, hemicelluloses 33.36±1.96% and lignin 4.12± 0.36% as substrate.